Trends of suicide rates by gender and residence in China from 2002 to 2019 - Yuhua Hu; Jie Pan; Rui Luo; Qianqian Yang; Zhiwei He; Hui Yuan; Guangren Zhou (Elsevier, 2023)
Objective: China has undergone tremendous social changes in the last few decades. This study aimed to research the trends of the suicide rates from 2002 to 2019, and to differentiate effects attributable to age, period, and cohort by gender and residence in China. Methods: Suicide mortality data were obtained from China's Ministry of Health Vital Registration System. Joinpoint regression model was used to estimate the average annual percentage change (AAPC) of the suicide rates and ratios by gender and residence. The age-period-cohort framework was performed to analyze the underlying mechanisms for suicide mortality trends. Results: Over the observation period, the significant decrease in suicide mortality rates in China for the economic development and urbanization was observed but to different degrees across gender and regional subgroups. The male-to-female ratio of suicide rates increased year by year (AAPC: 1.9%, 95% CI: 0.2% to 3.7%) while the urban-rural ratio changed little (AAPC: 0.9%, 95% CI: −1.8% to 3.7%). The age-period-cohort analysis revealed a marked increased effect of age and overall decreased effect of both period and cohort on suicide mortality rates. However, the recent cohort has presented an inversely increasing effect. Conclusion: The suicide rate has fallen sharply in China which has undergone tremendous socioeconomic changes. The varied changes in the suicide rate of different residence-, gender-, and age-groups as well as the age, period, and cohort effect on suicide risk further indicate the relationship of development and the suicide rates may be neither static nor identical on different subgroups in a rapidly changing society.